Ilmu Takhrij Al-Hadith: Pengertian, Sejarah dan Kepentingannya - Deraman, Fauzi (Jurnal Usuluddin, 2001)
Takhrij al-Hadith is part and parcel of the studies of Hadith. Its significance especially lies in analyzing the sanad of hadis which in turn establishes the level of authenticity of a hadith. This article attempts to give furthered elaboration on this aspect besides giving its historical background.